Metode Ijtihad Komisi Fatwa Majelis Ulama Indonesia - Rahmat, Rahmat (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2016)
The Fatwa Commision and the National Sharia Council are two institutions under the central of Indonesian Ulema Council (MUI). Its primary function is to issue fatwa (a binding ruling in religious matters) related with the fnance activities or product and sharia fnance service. The mechanism in making fatwa decision in both institutions under the Indonesian Ulame Council have a similarity in the collective IjtihÄd (jamaâ€™i) by using the IjtihÄd methodology such as bayani, taâ€™lili (qiyasi, istihsani, ilhaqi) and istihlasi. This method is used specially for contemporery matters or the matters are not discussed yet in detail among the mazhab ulame (school of thought concerning muslim law).Keyword : IjtihÄd, Fatwa